The compensation of the victimized accused after the establishment of his innocence in Islamic jurisprudence: a comparative study with Malaysian law - Ahmad Muhammad Husni al-Jufri, (Penerbit Universiti Kebangsaan Malaysia, 2010)
This study aims at shedding light on the extent of conformity between Islamic jurisprudence and Malaysian law with regard to the rights of the accused during the process of trial. An accused, for example, might suffer infringement of his rights which entitled him to compensation. The researcher investigated in both Islamic jurisprudence and Malaysian law, the meaning and principles of compensation which is mostly represented the form of financial compensation to the person whose rights have been infringed upon. But since Malaysian law and Islamic jurisprudence have not fixed a specific amount of money for compensation and has delegated the matter to the court, the researcher attempted to arrive at an approximate determination of the amount of compensation based on the study of various settled cases handled by Muslim jurists and Malaysian legal experts. The study depends on the deductive method to collect data from library sources both in Islamic jurisprudence and Malaysian law. In order to establish the relationship between Islamic jurisprudence and Malaysian law, the researcher also used a comparative method to compare and contrast the views of classical and contemporary Muslim jurists with the provision of Malaysian law on the issue under investigation. One of the objectives of this study is to encourage more research in positive legal studies involving comparisons between Islamic jurisprudence and Malaysian law. The study concluded that Malaysian law does not vary greatly from Islamic jurisprudence in terms of the personal and family rights of the accused with regard to compensation. Both Islamic jurisprudence and Malaysian law share the basic principle of compensation. Although Malaysian law has fixed the amount of compensation, it is not standard for all cases. Therefore, the judge has to fix the amount of compensation on the basis of the extent of harm. On the other hand, in Islamic jurisprudence this amount is not at all fixed. Rather, in every case a judge would determine the amount according to the extent of harm.